2006
DOI: 10.1007/s00221-006-0706-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the electrically evoked leg withdrawal reflex in cerebellar patients and healthy controls

Abstract: The aim of this study was to analyze the contribution of the cerebellum in the performance of the lower limb withdrawal reflexes. This has been accomplished by comparing the electrically evoked responses in cerebellar patients (CBL) with those in sex- and age-matched healthy control subjects (CTRL). The stimulus was applied to the subjects' medial plantar nerve in four blocks of ten trials each with switching the stimulus from one leg to the other after each block. Responses of the main muscle groups (tibial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…With respect to cerebellar involvement to voluntary movements and locomotion, we have only just begun to appreciate and pinpoint more precisely its modulatory actions (Bracha et al, 1999;Apps and Garwicz, 2005). For example, recent studies with human cerebellar patients indicated that the cerebellum is involved in the timing of withdrawal reflexes (Kolb et al, 2007). Other studies have indicated that the cerebellum is implicated in operant conditioning of the H-reflex (Chen and Wolpaw, 2005).…”
Section: Implications For Modular Cerebellar Functioningmentioning
confidence: 99%
“…With respect to cerebellar involvement to voluntary movements and locomotion, we have only just begun to appreciate and pinpoint more precisely its modulatory actions (Bracha et al, 1999;Apps and Garwicz, 2005). For example, recent studies with human cerebellar patients indicated that the cerebellum is involved in the timing of withdrawal reflexes (Kolb et al, 2007). Other studies have indicated that the cerebellum is implicated in operant conditioning of the H-reflex (Chen and Wolpaw, 2005).…”
Section: Implications For Modular Cerebellar Functioningmentioning
confidence: 99%
“…Its major functions range from motor and sensory timing [8] to calibration of movements and reflexes [9,10]. Lesions in the cerebellum typically cause hypotonia, dysmetria and dyscoordination [11].…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of the cerebellum as a putative structure for associative learning of motor actions and sensory stimuli has been studied extensively in humans using the method of classical conditioning, for review see [ 1 ]. Simple avoiding reflexes have been most frequently tested as for instance the eye-blink reflex [ 2 5 ] or the lower limb withdrawal reflex in both reclining subjects [ 6 9 ] and standing subjects [ 10 12 ]. Avoiding reactions involving larger and more complex behaviour like a postural reaction to prevent a fall have also been studied, e.g.…”
Section: Introductionmentioning
confidence: 99%